The Efforts of Al-Jihad Mosque's in Realizing the Taklim Assembly as an Islamic Education for Medan Baru Community - Muhammad Alpin Hascan (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2021)
A mosque is a place of worship that can be used for religious activities, especially Islamic education activities. This research objective was to discuss how the efforts of Al-Jihad Mosque foundation management in realizing the taklim assembly activities as Islamic education for the Medan Baru community. This research design was field research with a descriptive qualitative approach. The research subjects consisted of the head of da'wah (Islamic teachings) and education, treasurer, mosque takmir, and Medan Baru people. Data collection techniques used interview techniques, observation, and documentation. The data that has been collected was then reduced and presented, and conclusions were drawn. The results showed that the Al-Jihad mosque’s administrators were very active in realizing the taklim assembly to the maximum extent. It was evidenced by the busy schedule of the taklim assembly in a week. The scheduled research material had Islamic scientific studies such as fiqh, interpretation, monotheism, history, and other materials. The implementation of the taklim assembly began after the congregational prayer guided by the mosque takmir. The taklim assembly at the Al-Jihad mosque received a positive response and community support. Islamic youth communities and organizations also implemented religious activities, especially education at the Al-Jihad Mosque.